Petrology and Geochemistry of The Volcanic Arc Tarusan Pluton in Comparison to Lolo Pluton, West Sumatra - Irzon, Ronaldo; Syafri, Ildrem; Agustiany, Irfani; Prabowo, Arief; Sendjaja, Purnama (Jurnal Geologi dan Sumberdaya Mineral, 2019)
The Volcanic Arc Suite is the group of batholiths in the range of the Barisan Mountains and mostly denotes I-type affinity. Previous investigations of the intrusions in West Sumatra emphasized the crystallization age without completing geochemistry characteristics. No former study discussed a pluton which mapped in the Kota XI Tarusan District. This study explains the geochemistry and petrology of the Tarusan Pluton using polarized microscope, XRF, and ICP-MS at the Center for Geology Survey of Indonesia. The microscopic analysis confirms the granite character of the samples. Although both plutons are identified as I-type calc-alkaline series, the Tarusan Pluton is peraluminous granite whilst the Lolo Pluton denotes wider range from metaluminous to peraluminous of granodiorite to granite. Both the plutons are clearly classified as volcanic arc granitoid in the correlation to Volcanic Arc Suite of Sumatra. Negative Ba, Nb, and P anomalies together with positive K, Nd, and Y anomalies are pronounced on the two felsic intrusions. Negative Eu anomaly on the Tarusan Pluton but the positive one at the Lolo Pluton might explain different magma evolution process.Keywords: volcanic arc granite, geochemistry, Tarusan Pluton, Lolo Pluton.